1997
DOI: 10.1159/000119372
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Pituitary-Adrenal Response to Surgical Stress in Chronic Schizophrenic Patients

Abstract: We evaluated whether pituitary-adrenal response to surgical stress is modified in chronic schizophrenic patients. Twenty-two schizophrenic patients on chronic antipsychotic therapy of phenothiazine derivatives over 10 years underwent orthopedic surgery of the extremities under general anesthesia by isoflurane and nitrous oxide. In chronic schizophrenic patients, responses of plasma epinephrine, norepinephrine, ACTH and cortisol levels during surgical stress were significantly lower than those of control patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…The antipsychotic-induced changes in plasma NE levels are useful biological markers in predicting treatment [12]. On the Kudoh/Takahira/Katagai/Takazawa other hand, the plasma NE response to surgical stress in schizophrenic patients is lower [9]. The decreased NE response to surgical stress appears to be caused by antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antipsychotic-induced changes in plasma NE levels are useful biological markers in predicting treatment [12]. On the Kudoh/Takahira/Katagai/Takazawa other hand, the plasma NE response to surgical stress in schizophrenic patients is lower [9]. The decreased NE response to surgical stress appears to be caused by antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…However, under treatment with antipsychotics, there may be a decreased response to stressors. We previously reported that schizophrenic patients treated with antipsychotics had decreased plasma adrenocorticotropin (ACTH) and cortisol levels during surgery [9]. In this study, we investigated the relationship between postoperative confusion and the plasma NE, ACTH and cortisol response to surgery in chronic schizophrenic patients.…”
Section: Introductionmentioning
confidence: 98%
“…We previously postulated that neuroleptics inhibit the hippocampus, which plays an important role in the regulation of the HPA axis, and as the result, ACTH and cortisol secretion will be diminished by the reduced release of corticotropin-releasing hormone (CRH) [3]. Wik [21] demonstrated that down-regulation of cortisol secretion seems to result from prolonged neuroleptics, and hypothalamic corticotropin-release-inhibitory factor inhibits feedback-induced hypothalamic CRH production in response to decreased cortisol secretion.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that treatment of chronic schizophrenic patients was often complicated by autonomic dysfunction and decreased plasma adrenocorticotropin (ACTH) and cortisol levels during surgery [2,3]. Neuroleptic drugs are reported to suppress plasma cortisol levels and decrease the dexamethasone suppression test [4].…”
Section: Introductionmentioning
confidence: 99%
“…We reported that chronic schizophrenic patients were often complicated with autonomic dysfunction and a decrease in plasma ACTH and cortisol levels during surgery [1,2]. These are caused by potent antagonistic effects of antipsychotic drugs on the dopamine and noradrenergic receptors [3] and dysfunction of the hypothalamicpituitary-adrenal (HPA) axis [4].…”
Section: Introductionmentioning
confidence: 99%